Penegakan Hukum Tindak Pidana Perdagangan Barang Yang Tidak Berlabel Bahasa Indonesia: (Studi Kasus Perdagangan Makanan Yang Tidak Berlabel Bahasa Indonesia Di Kabupaten Bangka) - Cahyani, Intan; Toni; Armanda Agustian, Rio (BULLET : Jurnal Multidisiplin Ilmu, 2024)
This research focuses on law enforcement against criminal acts of trading food that is not labeled in Indonesian, with a case study in Bangka Regency. This research is motivated by the importance of using Indonesian language labels on food products in accordance with the provisions of Indonesian laws and regulations, especially to protect consumers from information that is misleading or difficult to understand. The aim of this research is to analyze the effectiveness of law enforcement carried out by law enforcement officers in Bangka Regency regarding the trade in food that is not labeled in Indonesian, as well as identifying factors that hinder and support law enforcement. The research method used is an empirical juridical method, with a case study approach. Data was collected through interviews with law enforcement officials, as well as through analysis of relevant legal documents. The results of the research show that law enforcement against this criminal act is still not optimal, as indicated by the fact that there are still food products circulating without Indonesian labels. Factors that hinder law enforcement include a lack of human resources, low legal awareness among business actors, and limitations in supervision. Meanwhile, supporting factors include collaboration between institutions and increasing public awareness through outreach. This research concludes that further efforts are needed to improve law enforcement, including increasing the capacity of law enforcement officers and educating business actors regarding the importance of compliance with food label regulations.